Dynamics of rice farmers responding to the challenges of global change (Case study in Kesugihan Kidul Village, Cilacap, Central Java) - Sholeh, Muh.; Suharli, Suharli; Segara, Nuansa Bayu; Suryadi, Yadi; Rusdini, Siti Ekowati (Edelweiss Applied Science and Technology, 2025)
The purpose of this study was to analyze the dynamics of rice farmers in responding to the challenges of global change, particularly the dynamics of the profile of rice farmers in Kesugihan Kidul Village, rituals in rice farming, shifts in farming culture, and the challenges of maintaining rice productivity. The approach used is qualitative with a case study method. The results of this study indicate: a) the profile of rice farmers shows diversity, which has implications for responsibilities in cultivating rice fields; b) farmers’ rituals in carrying out cultivation use stages that inherit the habits of previous generations while making several adaptations or adjustments; c) farmer culture has shifted from merely fulfilling daily needs to becoming profit-oriented by taking advantage of existing opportunities, including the expansion of livelihoods outside of farming; and d) the challenges farmers face in maintaining rice productivity are increasingly complex, both due to the narrowing of rice fields and the reduced quality of rice cultivation. Suggestions in this study are: a) a study of the life of farmers from the perspective of cultural geography is important to identify the diversity of farmer profiles in order to formulate policies that are more targeted; b) farmer rituals must be understood as part of the national system for increasing rice production; c) shifting farmers’ culture, both materially and immaterially, and addressing the challenges farmers face in maintaining rice production must be supported by the government through policies that are favorable.